Molecular investigation of tick-borne pathogens in ticks removed from tick-bitten humans in the southwestern region of the Republic of Korea. - Mi Seon Bang (Public Library of Science (PLoS), 2021)
In this study, we investigated the presence of tick-borne pathogens in ticks removed from tick-bitten humans in the southwestern provinces of the Republic of Korea (ROK). We identified 33 ticks from three tick species, namely Amblyomma testudinarium (60.6%), Haemaphysalis longicornis (27.3%), and Ixodes nipponensis (12.1%) in order of occurrence via morphology and 16S rDNA-targeting polymerase chain reaction (PCR). Tick-borne pathogens were detected in 16 ticks using pathogen-specific PCR. From the results, 12 ticks (36.4%) tested positive for spotted fever group (SFG) Rickettsia: Rickettsia monacensis (1/12), R. tamurae (8/12), and Candidatus Rickettsia jingxinensis (3/12). Three ticks (9.1%) were positive for Anaplasma phagocytophilum. In addition, three ticks (9.1%) tested positive for Babesia gibsoni (1/3) and B. microti (2/3). In conclusion, we identified three tick species; the most common species was A. testudinarium, followed by H. longicornis and I. nipponensis. SFG Rickettsia, A. phagocytophilum, and Babesia spp. were the most frequently detected pathogens in ticks removed from tick-bitten humans. To our knowledge, this is the first report of R. tamurae and Ca. R. jingxinensis detection in Korea. The present results will contribute to the understanding of tick-borne infections in animals and humans in the ROK.